Exploring the relationships between a map of altruism and a map of science. Issue 2 (13th April 2015) - Klavans, Richard; Boyack, Kevin W.
Abstract : EDITOR'S SUMMARY The science mapping community offers insights and points to trends in scientific inquiry by revealing connections among publications, authors, terminology and citation patterns. The authors applied the process of creating science maps to topics compiled by GuideStar to reveal altruistic motives driving nonprofit organizations (NPOs). From data mined from nearly four million web pages from 125, 000 NPO websites, they created a map of the altruistic motive space. Topic modeling from words on the web pages generated 1, 000 topics that were manually screened to yield 357 topics related to altruistic motives and their interrelationships. Nearly 100, 000 NPOs were positioned by topic on an overlay map, and map labels capturing altruistic motives were created by human analysis. The product was compared with a map of science based on Elsevier's Scopus database. The maps of altruism and science show the strongest link between the altruistic trait of caring and scientific research in medicine, health and neuroscience. Links are also demonstrated between other scientific areas and altruistic beliefs underlying environment, innovation and policy.